Accuracy of individual mandibular motion records using intraoral scanner for fixed implant- supported prosthesis designs: a comparative study - Bundhit Jirajariyavej; Panchanit Ounvorawong; Suchaya Pornprasertsuk-Damrongsri; Porntida Visuttiwattanakorn; Salisa Sriyarun; Pobploy Petchmedyai (BMC Oral Health)
Abstract Background Accurate occlusal registration is critical for successful dental implant treatments. Traditional mechanical articulation provides insight into occlusal relationships but cannot replicate complex mandibular movements accurately. CAD/CAM advancements, including virtual articulators, enable dynamic occlusion analysis using either average-value settings or individualized mandibular movement data, depending on the system used. Patient Specific Motion (PSM) technology, using intraoral scanners to record actual mandibular movements, offers enhanced functional occlusal design. Despite these advancements, challenges such as patient movement and limited residual dentition affect accuracy, highlighting the need for further research into dynamic occlusal registration methods. This study investigates the impact of different occlusal registration techniques on prosthesis design under varying conditions of missing teeth. Methods Ten participants were examined in an in-vivo study comparing the accuracy of three occlusal registration methods: 1) Static Occlusal Registration (SA), Dynamic Occlusal Registration including 2) Virtual Articulator (VA), and 3) Patient-Specific Motion (PSM). The tested models were simulated by digital tooth removal in three conditions of missing teeth, and 3-D deviations of occlusal contacts recorded before (reference) and after (tested) virtually tooth removal were assessed to reflect the accuracy of occlusal morphology reproduction. Results The root mean square (RMS), and percentage of In-Tolerance and Out-of-Tolerance of divided occlusal surface areas were analyzed and visualized using a color-coded deviation map. Statistically significant differences were observed between static and dynamic methods (p < 0.05), though no significant differences between the two dynamic methods. The PSM method exhibited the highest RMS values and a trend of negative deviations, while the VA method demonstrated the largest positive deviations. In terms of the effect of missing teeth, greater deviations were observed in models with more extensive tooth loss, particularly at the functional cusp areas, suggesting reduced accuracy in complex occlusal conditions. Conclusions This study confirms that different occlusal registration methods (STA, VA, PSM) significantly influence prosthesis design, with all showing clinically acceptable outcomes. PSM demonstrated advantages in customization and may improve treatment precision. Occlusal accuracy declined as the number of remaining teeth decreased, highlighting the importance of maintaining sufficient tooth contacts for reliable digital prosthesis design in partially edentulous cases. Trial registration This study was retrospectively registered and obtained approval from the TCTR Committee (TCTR20241116001, Date: 16/11/2024).